2017
DOI: 10.1080/19336918.2017.1377388
|View full text |Cite
|
Sign up to set email alerts
|

Calpain2 mediates Rab5-driven focal adhesion disassembly and cell migration

Abstract: The early endosome protein Rab5 was recently shown to promote cell migration by enhancing focal adhesion disassembly through mechanisms that remain elusive. Focal adhesion disassembly is associated to proteolysis of talin, in a process that requires calpain2. Since calpain2 has been found at vesicles and endosomal compartments, we hypothesized that Rab5 stimulates calpain2 activity, leading to enhanced focal adhesion disassembly in migrating cells. We observed that calpain2 co-localizes with EEA1-positive earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In addition to talin 1, tubacin reduced the levels of the small Rho GTPase Rab5C in the vimentin interactome, as well as Rab GDP dissociation inhibitor β (GDI2), a GDI that inhibits Rab5C. Rab5C is required for focal adhesion formation, as it activates the calcium-dependent protease calpain 2 and increases the turnover of focal adhesion proteins, including talin 1, to promote cell migration [32,35]. It is therefore possible that GDI-inactivated Rab5C is released from vimentin upon tubacin treatment, to result in increased outside-in signalling over focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to talin 1, tubacin reduced the levels of the small Rho GTPase Rab5C in the vimentin interactome, as well as Rab GDP dissociation inhibitor β (GDI2), a GDI that inhibits Rab5C. Rab5C is required for focal adhesion formation, as it activates the calcium-dependent protease calpain 2 and increases the turnover of focal adhesion proteins, including talin 1, to promote cell migration [32,35]. It is therefore possible that GDI-inactivated Rab5C is released from vimentin upon tubacin treatment, to result in increased outside-in signalling over focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cell migration requires coordinated detachment of the rear‐end and the disassembly of FAs, by mechanisms that remain poorly understood, although it is known to depend on FAK (Hamadi et al., ), calpain‐dependent proteolysis (Franco et al., ), and components of the endocytic machinery, such as dynamin, Dab2, clathrin, and Rab5 (Chao & Kunz, ; Ezratty, Bertaux, Marcantonio, & Gundersen, ; Ezratty, Partridge, & Gundersen, ; Mendoza et al., ). Particularly, recent studies from our laboratory showed that calpain2 is trafficked via early endosomes in a Rab5‐dependent manner, leading to FA disassembly (Mendoza et al., ).…”
Section: Role Of Cell Migration In Oral Wound Healingmentioning
confidence: 99%
“…A third possibility is that PI(3)P directly or indirectly affects the localization of Calpain 2 itself. Such a scenario is supported by data from non-neuronal cells suggesting that Calpain 2 activation is mediated by Rab5-mediated recruitment to early endosomes (Mendoza et al, 2018), that is, organelles that contain PI(3)P. These scenarios will need to be studied in detail in the future. Second, given the multiple roles of Cdk5 in presynaptic neurotransmission and SV cycling, it is possible that hyperactivation of Cdk5 impinges not only on SV endocytosis (Tan et al, 2003;Armbruster et al, 2013) but may involve additional target proteins such as voltage-gated calcium channels (Kim & Ryan, 2010), crucial factors for the regulation of presynaptic release probability.…”
Section: Discussionmentioning
confidence: 83%